IMPORTÂNCIA DA FAMILIA NO PROCESSO DE CUIDADOS: ATITUDES DE ENFERMEIROS NO CONTEXTO DA UNIDADE DE TERAPIA INTENSIVA - CHAVES, Rodson Glauber Ribeiro (2017)
Introduction: taking care of the family within the scope of nursing assures the care planning around this social group and is based on partnership which benefits at the same time professionals, patients and families with significant contributions towards the quality and safety of care, whilst it demands for nursing the recognition that all family members are recognized as attention receivers. Objective: identifying demeanors of nurses about the importance of families in the process of care according to the dimensions of the Scale Families’ Importance in Nursing Care – Nurses Attitudes in the context of intensive therapy. Methodology: transversal and descriptive study with quantitative approach of the population of 43 intensivist nurses from two public health institutions located in São Luís, Maranhão. Data collection was carried out from May to September 2016 supported by the scale Families’ Importance in Nursing Care – Nurses Attitudes (IFCE-AE). The IFCE-AE scale is auto fill Likert type composed of 26 items with four answer options (completely disagree, disagree, agree, and completely agree). The score of each item varies from 1 to 4 and of the complete scale IFCE-AE from 26 to 104 points. The attitudes of nurses face the importance of family care relations were categorized into three independent dimensions as defined by IFCE-AE: Family: dialogue partner and coping resource, family: resource in nursing care and family burden. The collected data were inserted in database using Microsoft Access ® Program and subsequently analyzed by the software STATA ® 12.1 and the results presented according to the attitudes of each dimension of IFCE-AE through the scores average. Results: according to the IFCE-AE scale nurses showed attitudes of family care, considering the total average score was 75.1 points. When categorized by dimension the average of the family dialogue partner and coping resource was 34.4 points; in the Family resource dimension of nursing care, the score was 30.0 points and in the Family Burden the average was 10.06 points. These results suggest that the nurses of the study recognize the importance of family care. Regarding the Family dialogue partner dimension and coping resource concerning to attitudes showed that 72.1% agreed to discuss with family members during the first contact, about the care process, it saves time in future work; 83.7% always sought to know who were the family members of the patient; the main attitudes on Family dimension: nursing care resources; 97.68% of nurses accept/stated that it is important to know who were the family members of the patient; 100% agreed that a good relationship with the members of the family would give them job satisfaction; 81.39% cite the presence of family members was important to them as a nurse; In the Family burden dimension 65.12% of observed nurses disagreed that the presence of family members makes their work difficult. Conclusion: According to nurses attitudes, it was observed that the characteristics that determine care guided by horizontal, vertical and complementary relationships are marked by the opening of new and diverse opinions as well as by the reception of them and involve the ability to value the experiences of family members, flexibility, tolerance and reflective thought.